The effects of interactive whiteboard with activity theory towards year five students’ motivation and performance in learning science - Yee, Ku Fang; Tasir, Zaidatun (Association for Scientific Computing Electrical and Engineering(ASCEE), 2023)
The purpose of this study is to investigate the effects of interactive whiteboard (IWB) with activity theory (AT) towards year five students’ motivation and performance in learning Science. This study explores the use and the effects of IWB in learning Science among Year 5 students. Learning activities that are based on Activity Theory approach have been designed to increase students’ motivation and performance in learning Science. Students' learning process and perceptions was analayse too. This study uses a quasi-experimental research design. The data collection process took about 4 weeks where a total of 40 students were selected as the sample of this research. The sample of this study consisted of Year 5 students of primary schools in Segamat District, Johor. Data were obtained through several instruments such as questionnaires and pre-test and post-test. Teaching and learning activities by using interactive whiteboard (IWB) with activity theory (AT) were designed and carry out during the research. The findings of this study will provide a vital contribution to the education field by giving a new option of choosing IWB to enhance teaching and learning process. Overall, The use of IWB integrated with Activity Theory in learning Science is able to increase students’ learning motivation. Students do better in class when they are motivated and have a positive attitude.